Trends in climate, socioeconomic indices and food security in Nigeria: Current realities and challenges ahead - Oderinde, Folasade Olubunmi; Akano, Oreoluwa Ibukun; Adesina, Francis Adeyinka; Omotayo, Abiodun Olusola (Frontiers in Sustainable Food Systems, 2022)
Food security in Nigeria is presently in dire strait owing to several factors, such as skyrocketing energy prices, climate change, and terrorism. This study is aimed at revealing the role of the aforementioned factors in shaping food affordability and availability in the country. The study used descriptive statistics and coefficients of variation and determination to ascertain the change in the trend in these factors and their correlates to food security over time. From the results of our research team, we inferred that temperature increases, political instability, rising food prices and erratic energy supply have had distressing consequences in the areas of affordability, availability and stability of food supplies. We conclude that a rapidly growing population such as Nigeria's would need crucial interventions in increasing food production, mitigating the impacts of climate change, and buffering energy supplies. Ultimately, Nigeria needs to overhaul the important components of her food systems and the respective linkages between these components in order to ensure food security for the entire population.